495 Developing deprescribing resources for older people with polypharmacy living in primary care: using co-design and logic modelling. (13th April 2023) - Okeowo, D A; Fylan, B; Quyyam, F; Butt, N; Mills, T; Zaidi, S T R; Alldred, D P
Abstract: Introduction: Proactive deprescribing – identifying and discontinuing medicines where harms outweigh benefits (1) – can minimise problematic polypharmacy, but it has not been routinely implemented into practice and can have risks. There are complex barriers and facilitators to deprescribing, however there is little evidence about how to overcome such barriers or promote facilitators and what resources are needed to safely and routinely implement deprescribing in primary care. Aim: To co-design deprescribing resources that aid the implementation of safe and routine deprescribing in primary care. Methods: Community-dwelling patients aged ≥65 years taking ≥5 medicines, community pharmacists, primary care pharmacists and GPs were invited to co-design workshops conducted in July 2022. Participants were recruited through social media and research networks. This project did not require formal ethical approval as it was a service improvement initiative. Two online workshops were facilitated using Microsoft Teams and Miro boards and were supported by a Patient and Public Involvement representative. The first workshop comprised a briefing about findings from a scoping review, systematic review and interview study with patients and healthcare professionals about deprescribing implementation, followed by idea generation through group activities. Potential resources identified were collated and, through discussions with the wider research team, two were prioritised to be further developed. The second workshop used storyboards to further understand and add detail to how the resources chosen would aid the implementation of routine and safe deprescribing in primary care. A logic model was then developed for the resource developed in the workshop. Results: Five patients, two GPs, one primary care pharmacist and one community pharmacist took part. In the first workshop, participants identified:(a) patients were suitable advocates for their own health and could initiate conversations about medicines necessity but may need prompts or suggested questions to do so; and (b) community pharmacist follow-up with patients post-deprescribing could help ensure safe deprescribing and facilitate appraisal of deprescribing for future learning. In the second workshop, five questions patients could ask healthcare professionals during everyday interactions and two questions patients could ask during a medication review were developed to stimulate conversations on the necessity of medicines. A storyboard about how community pharmacy could act as a safety net post-deprescribing was developed and refined, following the workshop, into a Real World Logic Model (2) to explain how this safety net could work, the safety net context, and the anticipated outcomes. Conclusion: Patients may be able to stimulate conversations on medicine necessity leading to routine deprescribing, whilst community pharmacists could potentially help ensure deprescribing safety. Questions were developed to empower patients to raise the issue of medicines necessity, and a logic model demonstrating community pharmacists as a deprescribing safety net were developed to aid safe and routine deprescribing in primary care. The co-participation of patients and healthcare professionals ensured that both groups' values and priorities informed intervention development. However, the acceptability and usability of the co-designed interventions cannot be known until feasibility testing has been conducted. References: 1. Scott IA, Hilmer SN, Reeve E, Potter K, Le Couteur D, Rigby D, et al. Reducing Inappropriate Polypharmacy: The Process of Deprescribing. JAMA Internal Medicine. 2015;175(5):827-34. 2. Mills, T., Shannon, R., O'Hara, J., Lawton, R., & Sheard, L. (2022). Development of a 'real-world' logic model through testing the feasibility of a complex healthcare intervention: the challenge of reconciling scalability and context-sensitivity. Evaluation, 28(1), 113–131.